Outpatient treatment of low-risk neutropenic fever in cancer patients using oral moxifloxacin - Chamilos, G.; Bamias, A.; Efstathiou, E.; Zorzou, P.M.; Kastritis, E.; Kostis, E.; Papadimitriou, C.; Dimopoulos, M.A. (Cancer, 2005)
BACKGROUND. Oral-based antibiotic therapy is the standard of care in the management of cancer patients with low-risk neutropenic fever. Nevertheless, to the authors' knowledge, the best antibiotic regimen and the feasibility of ambulatory treatment have not been clearly defined. METHODS. The authors evaluated the efficacy and safety of moxifloxacin as outpatient treatment in cancer patients with febrile neutropenia who were selected according to the recently proposed Multinational Association for Supportive Care in Cancer (MASCC) risk assessment model. Moxifloxacin was given at a dose of 400 mg orally once daily. RESULTS. Fifty-four patients with solid and hematologic malignancies, the majority of whom (84%) had advanced disease, were included in the current study. The median neutrophil count at the time of study entry was 340/mm3 (range, 20-950/mm3) and the median duration of neutropenia was 4 days (range, 3-14 days). Of 55 neutropenic episodes, 50 (91%) had a successful outcome with a median time to defervescence of 2 days (range, 1-5 days). A multivariate analysis indicated that severe neutropenia (an absolute neutrophil count of < 100 mm3) was the only independent factor associated with treatment failure (P < 0.04). Moxifloxacin was found to be well tolerated and there were no infectious deaths reported. CONCLUSIONS. The results of the current study demonstrated that moxifloxacin was a highly effective and safe regimen in the outpatient treatment of cancer patients with febrile neutropenia. © 2005 American Cancer Society.
Keywords: Cancer; Moxifloxacin; Neutropenic fever; outpatient